Discovery of New Red Stars with Digitized Plates of the μ Cephei Ragion - Karapetyan, E. L.; Gigoyan, K. S.; Kostandyan, G. R.
The results of the spectral classification of 357 red stars observed in the Cepheus region are presented. 257 of the featured stars are included in the KP2001 catalogue. We found the remaining 100 red stars as a result of digitizing plates used in compiling the KP2001 catalog. All star data is taken from the GAIA DR3 database. These stars are most likely giants and supergiants. None of them were included in the catalog of variable stars. It has been suggested that further research may reveal variability in many of these.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture